2020
DOI: 10.1016/j.str.2020.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Structural Modeling of Full-Length LRH-1 Reveals Inter-domain Interactions Contribute to Receptor Structure and Function

Abstract: Highlights d Integrated structural model of full-length monomeric nuclear receptor LRH-1 d Model accurately predicts a novel inter-domain charge clamp d DNA binding and transcriptional activation domains dock via conserved helices d Binding of a known transcriptional co-regulator alters LRH-1 inter-domain dynamics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 93 publications
(103 reference statements)
2
47
0
Order By: Relevance
“…3 A, B) typical for nuclear receptor ligand binding domains, distributed into three layers, with fully ordered helices 1 and 2 ( Fig. 3 C) typical for the subclass of nuclear receptors which SF-1 belongs (NR5A) ( 15 , 40 , 43 , 44 ). The 12 alpha helices end with the C-terminal helix 12, which helps form the site that binds the PGC1α coactivator peptide ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 A, B) typical for nuclear receptor ligand binding domains, distributed into three layers, with fully ordered helices 1 and 2 ( Fig. 3 C) typical for the subclass of nuclear receptors which SF-1 belongs (NR5A) ( 15 , 40 , 43 , 44 ). The 12 alpha helices end with the C-terminal helix 12, which helps form the site that binds the PGC1α coactivator peptide ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Those data suggest some form of interdomain communication must occur between the SF-1 ligand-binding domain (LBD) and DNA-binding domain (DBD), since the R255 amino acid is located in the LBD, but changes function of the DBD. We recently developed a structural model describing LBD-DBD communication for full length LRH-1 (NR5A2), a close homolog of SF-1 (NR5A1) (48). That model of LRH-1 shows LBD helix 2 is a key site for an interaction between the LBD and DBD, and that disrupting the interdomain interaction on the LBD side, alters DNA-binding on the DBD side of the interface (48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using similar techniques, Seacrist et al . found that monomeric NR LRH1 adopted a more globular complex on DNA such that the LRH1DBD transmitted information to the LRH1LBD [47]. In contrast, our studies suggest that RORγ becomes elongated upon DNA recognition effectively uncoupling the two domains.…”
Section: Discussionmentioning
confidence: 62%